2018
DOI: 10.1371/journal.pone.0193092
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cognitive impairment and functional limitation on depressive symptoms among community-dwelling older Korean immigrants in the U.S.

Abstract: The present study examined the effects of cognitive impairment and functional limitation on depressive symptoms among older Korean American immigrants. The sample was drawn from a cross-sectional survey of 210 older Korean immigrants (aged 65 years or older) in Los Angeles County. Based on robust hierarchical regression, the study found that cognitive ability and functional status were significant explanatory factors related to depressive symptoms among older Korean immigrants. In addition, the interaction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
10
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 21 publications
3
10
1
Order By: Relevance
“…For establishing the construct validity, significant relationships were detected between MoCA-5-min and various comparing constructs, including age, education and functional ability. However, the relationships between MoCA-5-min with depression and mental wellbeing were not significant, which was contradictory to the hypothesized relationships suggested by the available evidence [39,40].…”
Section: Discussioncontrasting
confidence: 86%
“…For establishing the construct validity, significant relationships were detected between MoCA-5-min and various comparing constructs, including age, education and functional ability. However, the relationships between MoCA-5-min with depression and mental wellbeing were not significant, which was contradictory to the hypothesized relationships suggested by the available evidence [39,40].…”
Section: Discussioncontrasting
confidence: 86%
“…At the same time, there is some evidence to support the generalizability of findings from PRO linguistic validation studies to Korean speakers residing both in Korea and in the United States. 20 Third, although our sample was quite diverse with respect to tumor type, some specific tumor subgroups, such as those with brain or CNS tumors, were under-represented in the sample. This limitation might be important because patients with those tumors may suffer from cognitive deficits that could affect comprehension of self-report measures.…”
Section: Discussionmentioning
confidence: 95%
“…Functional decline also acts as an explicit cue signifying the progressively deteriorating nature of dementia 86 . However, a systematic review 87 indicated that the positive cognitive benefits of most of the studied cognitive training did not always translate into instrumental activity of daily living in people with cognitive impairment 85 . Therefore, incorporating these active strategies to translate acquired cognitive skills into daily activities may explain the superior performance of multimodal interventions.…”
Section: Discussionmentioning
confidence: 99%